Transformational leadership at the Universidad Nacional del Centro del Perú, according to the perception of teachers - Laredo-Cardenas, Reyna I. (2021)
Objective. To determine the level of transformational leadership predominant in the authorities of the Universidad Nacional del Centro del Perú in Huancayo, according to the perception of teachers. Methods. The study had a quantitative approach, basic type and non-experimental, cross-sectional and simple descriptive design. The population consisted of 823 teachers of the University, distributed among 25 faculties. The sample consisted of 150 teachers, selected by non-probabilistic sampling by quotas. For data collection, the abbreviated multifactorial leadership questionnaire (MLQ short form 5X) of Bass and Avolio (1997) was applied. Results. A preponderance of high level of transformational leadership was found (46.7 %), followed by moderate level (32 %), low level (12 %), very high level (6.7 %) and very low level (2.7 %). Conclusion. According to the perception of teachers, a high level of transformational leadership predominates in the authorities of the Universidad Nacional del Centro del Perú in Huancayo.